Nanomodification of mineral binders - Derevianko, Viktor; Дерев’янко, Віктор; Kondratieva, Nataliia; Кондратьєва, Наталія; Volkova, Viktorija; Волкова, Вікторія; Hryshko, Hanna; Гришко, Ганна (My University, 2021)
In the result of researches performed on the directed regulation of properties of gypsum binders, it was determined that the specific surface of various anisotropic surfaces regulates the shape of crystals as well as kinetics of their formation and growth. It has been established that the process of hydration and formation of gypsum binders can be regulated through the size of the specific surface, parameters of nanoadditives as well as through the change of concentration in solution. The influence of micro- and nanoadditives on the change of the system surface energy, as well as on introduction of plasticizer and change of time solution is in the supersaturated state (which increases the number of nuclear centers of crystallization) has been established experimentally and theoretically proved. У результаті проведених досліджень спрямованого регулювання властивостей гіпсових в'яжучих встановлено, що питома поверхня різних анізотропних поверхонь регулює форму кристалів, а також кінетику їх утворення та росту. Встановлено, що процес гідратації та утворення гіпсових в’яжучих можна регулювати розміром питомої поверхні, параметрами нанодобавок, а також зміною концентрації в розчині. Експериментально та теоретично встановлено вплив мікро- та нанодобавок на зміну поверхневої енергії системи, а також на введення пластифікатора та зміну часу перебування розчину в перенасиченому стані (що збільшує кількість ядерних центрів кристалізації) встановлено експериментально і теоретично доведено.
Наномодифікація мінеральних в'яжучих
Volkova V. ORCID ID: 0000-0002-1883-1385 Hryshko H. ORCID ID: 0000-0001-7046-1177
Keywords: hydration process; процес гідратації; properties of gypsum binders; властивості гіпсових в'яжучих; micro and nano additives; мікро- та нанодобавки